A multicomponent TiZr-based amorphous brazing filler metal for high-strength joining of titanium alloy. (May 2016) - Pang, Shujie; Sun, Lulu; Xiong, Huaping; Chen, Chen; Liu, Ying; Li, Haifei; Zhang, Tao
Abstract: High contents of Cu and Ni in Ti-based brazing filler metals (BFMs) usually cause the formation of brittle intermetallics in titanium alloy brazed joints, which weakens the joint mechanical properties. In this work, a novel multicomponent Ti50 Zr27 Cu8 Ni4 Co3 Fe2 Al3 Sn2 Si1 (at.%) amorphous BFM with low total content of Cu and Ni and low liquidus temperature was designed and synthesized by melt spinning. The Ti–6Al–4V joints brazed with this amorphous BFM exhibited high shear strength up to ~ 413 MPa, which is mainly attributed to the reduced amount of intermetallics in the braze zone due to the low contents of Cu and Ni in the BFM. Graphical abstract: